RETAIL BANKING PROFITABILITY IN THE CONTEXT OF FINANCIAL SECTOR TRANSFORMATION (Academicia Globe: Inderscience Research, 2025)
The study investigates the determinants of retail banking performance using econometric methods applied to data from JSB “Turonbank” for the period 2016–2024. The results demonstrate that retail lending is the main driver of profitability, while deposit mobilization and digital transformation variables (remote banking users, card circulation) provide complementary but lagged effects. All estimated models fulfill the Gauss–Markov conditions, confirming the efficiency and reliability of the obtained coefficients. The Random Effects model was found to be the most consistent estimator, and the ARDL specification validated the short-run elasticity and dynamic stability of profit responses to lending growth. This research contributes to the empirical literature on bank profitability in emerging economies by providing micro-level evidence from Uzbekistan’s retail banking sector. The findings have practical implications for credit policy, risk management, and digital finance strategies, offering a methodological foundation for long-term performance forecasting and sustainable financial development.